KETELITIAN METODE EMPIRIS UNTUK MENGHITUNG DEBIT BANJIR RANCANGAN DI DAS BANGGA - Marcelia, Marcelia; Haricahyono, Totok; Abu, Asnah (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2014)
Characteristics of Bangga watershed that involves the shape, topography, type of soil, vegetation and areal usage, tends to enable the occurrence of run-off and erosion in the event of high rain fall. Therefore, it requires a flood design debit measurement to obtain the value of flood design for its river basin. The method used in this research is to compare the design values of the rain fall data using Rational, Melchior, Weduwen, Haspers and Unit Synthetic Hydrograph of Nakayasu methods towards the measured flood design debit using frequency distribution methods according to several statistical parameters. The results of the comparison of several methods towards flood debit design obtained from measured debit data using log Pearson III are: for the largest deviation is 2278.21 % for 2 years return period using Haspers method, whereas for the smallest deviations was obtained using Rational method which was 23.41Â  %, as well as for 5, 10, 25, 50 and 100 years return period, the values were 5.21 %, -2.38 %, -9.40 %, -13.38 % and -16.64 % respectively, hence it can be taken into conclusion that Rational method could be applied in designing water buildings in Bangga river basin. Keywords: design flood discharge, rainfall data, discharge data (measured)